Biological Productivity of Shorea Plantations - Raman, S. S. (Indian Forester, 1976)
Even-aged series of Shorea plantations are investigated for evaluation biological production. Leaf area index and stand basel area of have reached peak values over 18 years of tree growth. Tree biomass of 137 ton/ha and net primary productivity of 14.62 ton/ha/year are reported for sal plantations in Tilkonia range, Gorakhpur Forest Division. Effects of stand age on biomass production, distribution and production ratios are documented for man made forests of sal. Sal stands belonging to advanced ages (40-70 year) need further study to definitely establish trends of annual productivities in relation to age sequence.